2018
DOI: 10.1007/s10468-018-9794-4
|View full text |Cite
|
Sign up to set email alerts
|

Lie Algebras of Slow Growth and Klein-Gordon PDE

Abstract: We discuss the notion of characteristic Lie algebra of a hyperbolic PDE. The integrability of a hyperbolic PDE is closely related to the properties of the corresponding characteristic Lie algebra χ. We establish two explicit isomorphisms:1) the first one is between the characteristic Lie algebra χ(sinh u) of the sinh-Gordon equation uxy = sinh u and the non-negative part L(sl(2, C)) ≥0 of the loop algebra of sl(2, C) that corresponds to the Kac-Moody algebra A(1) 12) the second isomorphism is for the Tzitzeica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The first idea of the proof [33], [34] is to represent the characteristic Lie algebra (sinh( )) as the Lie algebra ℒ ( 0 , 1 , 2 ) generated not by two, but by three elements 0 , 1 , 2 . The advantage of the representation (sinh( )) = ℒ ( 0 , 1 , 2 ) is the following two commutation relations:…”
Section: New Operators Can Be Written As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first idea of the proof [33], [34] is to represent the characteristic Lie algebra (sinh( )) as the Lie algebra ℒ ( 0 , 1 , 2 ) generated not by two, but by three elements 0 , 1 , 2 . The advantage of the representation (sinh( )) = ℒ ( 0 , 1 , 2 ) is the following two commutation relations:…”
Section: New Operators Can Be Written As Followsmentioning
confidence: 99%
“…In paper [21], the characteristic algebra of the sine-Gordon equation, having a growth rate of 3 2 was studied, and in [25], there was studied the characteristic algebra of the Tzitzeica equation growing at an average rate of 4 3 . In papers [33], [34] infinite linear bases for these Lie algebras were constructed and it was shown that they are isomorphic to the nonnegative part of the loop algebra s (2, C) ⊗ C[ , −1 ] and to the twisted loop algebra of the simple Lie algebra s (3, C), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These equalities means that for any Z ∈ L y and any a ∈ A, the element aZ ∈ L y . In this case the algebra L y is called the Lie-Rinehart algebra [20,22].…”
Section: Introductionmentioning
confidence: 99%
“…20) Now we will work with equations (2.10)-(2.12) to clarify functions F 2 , F 4 . Let us express F 4,uz , F 2,uz from (2.10) and substitute them into (2.12).…”
mentioning
confidence: 99%
“…An effective criterion of the Darboux integrability of the system is connected with properties of an associated algebraic structures. More precisely, the characteristic Lie-Rinehart algebras [20,21] assigned to both characteristic directions have to be of a finite dimension. Since the obtained hyperbolic system is of a very specific form, this allows us to study effectively the characteristic algebras.…”
Section: Introductionmentioning
confidence: 99%